FACTORS FOR THE DEVELOPMENT OF PUBLIC TRANSPORT IN UZBEKISTAN (American Journal of Research in Humanities and Social Sciences, 2025)
This scientific article analyzes the factors of development of the public transport system in Uzbekistan. The article considers the economic and social significance of the transport system, as well as the current state and development prospects of public transport in the country. The effective organization of transport links between cities and districts, the environmental aspects of the public transport system, its impact on the economic development of cities are analyzed. In particular, recommendations are made on the digitization of public transport, the introduction of environmentally friendly technologies and improving the quality of service. The article also highlights the importance of cooperation between the public and private sectors in the development of public transport.